Stability and adaptability assessment of red onion genotypes using AMMI, GGE, BLUP, and multivariate indices - Gupta, Amar Jeet; Aribenchi, Kavya V.; Benke, Ashwini; Kaldate, Supriya; Hulagannavar, Pushpa; Kale, Rajiv; Mahajan, Vijay (Frontiers in Plant Science, 2025)
IntroductionRed onion (Allium cepa L.) productivity and quality are highly contingent on environmental context, necessitating rigorous genotype evaluation across sites and seasons.MethodsTwenty-four red onion genotypes were evaluated in multi-environment trials (METs) across fixed, agro ecologically diverse Indian locations, during two consecutive rabi seasons (2023-24). As the same locations were used in both years, they were treated jointly as eight distinct environments (E1-E8) to quantify genotype × environment interaction (GEI) and identify broadly or specifically adapted cultivars. An integrated analytical pipeline combined GGE and AMMI biplots with mixed-model BLUPs, including the Harmonic Mean of the Relative Performance of Genotypic Values (HMRPGV), alongside multivariate indices Genotype-by-Trait (GT), Genotype-by-Yield × Trait (GYT), and Multi-Trait Genotype-Ideotype Distance Index (MGIDI) to facilitate multi-trait selection across marketable yield (MY), days to harvest (DTH), average bulb weight (ABW), total soluble solids (TSS), double bulb formation (DB), and thrips incidence (TI).ResultsPooled ANOVA and GGE analyses indicated significant genotype, environment and GEI effects for all traits. The first two GGE axes captured substantial variation of 56.7% (MY) to 86.6% (DB) of variation, supporting reliable biplot interpretation. Across complementary models, Bhima Shakti (G24), RO-1672 (G11), Bhima Kiran (G23) and RO-1773 (G19) consistently ranked among the top performers, exhibiting desirable stability profiles; MGIDI index further supported these selections. GGE delineated three mega environments for MY, DTH and TI, with vertex genotypes varying by trait, while AMMI biplots identified genotypes proximate to the origin as broadly stable. Environment ranking emphasized E6 (ICAR-DOGR, Pune) as most informative (discriminative and representative) for MY.Discussion/ConclusionIntegrating BLUP with AMMI, GGE and multi-trait selection indices enhances accuracy of genotype recommendations, enabling the identification of high-performing and stable red onion cultivars across diverse Indian agro-ecologies.